Pengaruh pusingan kerja terhadap prestasi kerja penjawat awam dalam kalangan perkhidmatan awam negeri Melaka - Md Yusof, Mohd Asri (2023)
In the face of the increasingly challenging environment of globalization, every organization needs to take proactive action to ensure that the human capital it owns, could move in line with current developments. Job performance is an important indicator to measure the effectiveness of the public sector service delivery system. For that purpose, this study is to test empirically the influence of human resource development approach that is the job rotation on the job performance of the public sector of the Civil Servants in the State of Melaka. This study examines the role of job motivation and job satisfaction as mediators in the relationship between job rotation and job performance. This study is a quantitative study that uses a descriptive survey study design. The population of this study is 403 officers among the Administrative Assistant (Clerical/Operation) in 17 Melaka State Departments with a sample size of 198 respondents. This study has used a human capital development and human capital transformation to evaluate job rotation practices. While the job performance measurement tool involves of work production dimension, knowledge and skills dimension as well as the personal quality dimension. For job motivation variables, the Work Extrinsic and Intrinsic Motivation Scale (WEIMS) was used, while the Job Satisfaction Survey (JSS) was used to measure job satisfaction variables. The response to the study items was based on five Likert scale points which were further analyzed through the IBM SPSS Statistics version 25 and PROCESS for SPSS to test the data obtained. The findings showed that the job rotation has a positive and significant relationship on job performance. In addition, this study also shows that job motivation and job satisfaction are mediators to the relationship between job rotation and job performance. The results of the study helped to give a clearer view regarding the influence of job rotation, job motivation, job satisfaction as well as individual job performance. Overall, this study summarizes the impact of research from theoretical and practical aspects that touch on the factors of job rotation, job motivation, job satisfaction and job performance. The findings suggest that human resource management inject the significant improvement in job performance through job rotation practices as an organizational holistic approach in the formation of human capital and the transformation of high-performing human capital. The Malaysian government as a stakeholder need to strengthen the implementation of job rotation as an important agenda to improve the civil servants job performance to provide public services that exceed the expectation of the people.